One-step CVD fabrication and optoelectronic properties of SnS2/SnS vertical heterostructures. Issue 8 (4th June 2018) - Li, Mingling; Zhu, Yunsong; Li, Taishen; Lin, Yue; Cai, Hongbing; Li, Sijia; Ding, Huaiyi; Pan, Nan; Wang, Xiaoping
Abstract : A high-quality vertical SnS2 /SnS heterostructure with excellent photoresponse has been fabricated and demonstrated. Abstract : Heterostructures constructed by two-dimensional (2D) material layers, which are usually prepared via a transfer/stacking method or van der Waals epitaxy, have achieved significant success in various optoelectronic devices including solar cells, light-emitting diodes and photodetectors. However, to date, most of these heterostructures comprise 2D materials with a similar crystal structure. Thus, preparation of heterostructures with different crystal structures is desirable but still a great challenge. Herein, we report a one-step CVD strategy to successfully grow SnS2 /SnS vertical heterostructures on a mica substrate. Raman spectroscopy, atomic force microscopy (AFM) and transmission electron microscopy (TEM) characterizations reveal that the heterostructure is formed by stacking of pyramid-shaped SnS2 of the hexagonal structure onto the rhombus SnS flake of the orthorhombic structure. The photodetector based on the SnS2 /SnS heterostructure demonstrates high optoelectronic performance: a 27.7 A W −1 photoresponsivity, 2.2 × 10 3 on/off ratio, less than 10 ms response time and 2.1 × 10 10 jones specific detectivity. The superior performance originates from the high crystal quality of the as-grown heterostructure and its vertical device architecture. This study can expand our capability to fabricate a variety of two-dimensional heterostructures and make these heterostructures highly desirable as novel building blocks for potential applications in electronic and optoelectronic devices.